UTILIZATION OF ARTIFICIAL INTELLIGENCE IN PUBLIC SERVICES THROUGH THE CHATBOT “JESSICA” ON THE JOGJA SMART SERVICE APPLICATION IN YOGYAKARTA CITY - Fattah, Arsianita Nur; Alifia Ainun Rizky; Eureka Try Zarazwanty R. Laega (Gema Kampus IISIP YAPIS Biak, 2026)
The use of artificial intelligence (AI) in public services has become a strategic innovation in advancing an efficient and responsive digital government. One increasingly prevalent AI implementation is the use of chatbots as virtual assistants to provide public information services. This study aims to analyze the use of the “JESSICA” chatbot in the Jogja Smart Service (JSS) application in Yogyakarta City to improve the efficiency and responsiveness of public services, and to identify challenges and potential developments. The Research method is a literature review that examines scientific articles, previous Research results, and documentation related to chatbot implementation in the public sector. The results show that chatbots play an important role in improving service efficiency by automating information delivery, reducing officials’ workload, and optimizing organizational resources. In terms of responsiveness, chatbots can provide services quickly, consistently, and in real time, thereby improving the quality of interactions between the government and the public. However, the JESSICA chatbot still faces several limitations, including limited coverage across the JSS application and website, reliance on database quality, and the need for continuous content and system updates. Furthermore, institutional readiness and human resource capacity are also crucial factors in determining the success of chatbot implementation. Therefore, future development of the JESSICA chatbot should focus on strengthening technical aspects, expanding service channels, and improving internal governance and policies. This Research is expected to provide conceptual and practical contributions to the development of a more efficient, responsive, inclusive, and sustainable digital public service model at the regional level.